Electrospun Nanofiber Composite for Levofloxacin in Ocular Drug Delivery - Sangole, Shrinivas; Salave, Sagar; Rana, Dhwani; Shah, Srushti; Medhe, Tanvi P.; Benival, Derajram (Pharmaceutical Nanotechnology, 2022)
Background: Levofloxacin is available in the form of an eye drop solution for the treatment of ocular bacterial infection and inflammatory diseases. Below 5% of the drug gets absorbed after topical application of eye drop. The major portion of administered drug either comes out from the eye or drains out by the nasolacrimal duct, which results in poor bioavailability. Objective: We aim to prepare a polymeric ocular insert containing levofloxacin as a drug prepared by the electrospinning technique that can release the drug for an extended duration. Methods: Electrospun nanofiber sheets were prepared using hydroxypropyl cellulose and polycaprolactone polymer. Drug content was analysed by HPLC. Nanosheet was examined by DSC and FTIR for compatibility study. Optimized nanosheet was further studied for weight uniformity, swellability index, surface pH, and in-vitro drug release. The morphology of the prepared sheets was examined using optical microscopy and SEM analysis. Results: The uniform, beadles, and continuous nanofibers were obtained by electrospinning. From the DSC and FTIR data, it was proved that drugs and polymers were compatible in nanosheets. Drug content and % drug loading in the electrospun sheets were found to be 101.70% and 4.33%, respectively. The thickness of the sheets was around 0.31± 0.04 mm and the swelling index was observed at 566.66% after 30 min. The surface pH of the ocular insert was found to be 6.81 and 6.83 after 30 min and 24 h., respectively. In-vitro drug release showed that 99% of the drug was released in 8 h. Conclusion: A prepared nanocomposite sheet can be used for the sustained drug delivery of levofloxacin in ocular eye disease, reducing the dosing frequency and improving patient compliance.
Keywords: electrospinning